Ballad of the Punished Daughter: Possibilities of Interpretation - Liugaitė-Černiauskienė, Modesta (Tautosakos darbai, 2014)
This analysis was inspired by the still problematic role of the ballads in the corpus of Lithuanian folksongs. Jonas Balys has once attempted tackling this problem by introducing a category of the “narrative folksongs”. On the other hand, ballads may look like a kind of methodological relic in the system of the Lithuanian folksong catalogue, i. e. something that is left over after all the other pieces of folksongs have been coherently systematized. Therefore the ballad research inevitably involves making certain working assumptions. It seems worthwhile discerning (1) layer of the ritual symbolism, which is typical to the ballads (just like to the folksongs), and (2) the ballad-like rendering of an individualized event. In this article, a single type of the Lithuanian ballads is dealt with as a characteristic case, which is approached from a more distant perspective, that is, by taking into account a broader area. The ballad of the punished daughter Augo ant dvaro liepelė (A Linden Tree Was Growing in the Yard) has similarities to the Belorussian ballad Cichonia (Ціхоня). In both of them, the pragmatic didactical intention has been subdued, which makes these ballads different from thematically similar pieces in folklore of other countries. The Belorussian ballad contains distinct archaic motives: e. g. the magic power of words, the brother marrying his sister off, the marriage with the Danube River, and turning the human into a plant. The motive of the marriage with the Danube River is essential for understanding the ballad. It presents a distinct metaphor of drowning, of perishing. The Belorussian ballad involves the motive of the mythical wedding, which can be found in folklore of various peoples (including Lithuanians). The motive of marrying the Danube River transfers the ballad’s plot onto the metaphorical level. The Lithuanian ballad contains the following significant motives: expression of the father’s will, an ambivalent role of the brother, the capacity of the human being to turn into an animal (fish), music accompanying the people’s actions, and symbolic timing of the ballad’s events. It seems plausible to assert that the ghastly core of the ballad’s plot is cruelty of one family member (the father) towards another one (the daughter). Just like in the Belorussian ballad, in the Lithuanian one the role of the brother(s) is ambivalent: first, reporting the sister to the farther, and afterwards, reproaching the farther for being too strict and punishing his daughter too hard. Two other motives belong to the symbolic layer: the music accompanying the people’s actions (the ringing of bells, the pipes being blown), and the time of the events (Saturday and Sunday, belonging to the cycle of the wedding rituals, and, more rarely, Monday and Friday). Quite a few variants can be characterized by a tendency to mitigate the storyline describing the daughter’s offence and the punishment executed by her father, and putting forward the symbolism of the wedding transformation instead. Some variants belonging to the type in question lack the ballad-like rendering in general: here, the drowning of the daughter is replaced by “drowning” of her “young days”, her youth, or her golden ring. There is one variant that makes drowning and marrying off sound like synonyms. The variation of this ballad type, its connections to the Belorussian ballad, and various manifestations of the central motive (drowning / marrying the Danube River) discerned in it, and finally, associating the girl to the idea of an offering, point out to different possibilities of interpretation. On the one hand, the role of the ritual symbolism can be emphasized, thus placing the ballad Augo ant dvaro liepelė into the sphere of gravitation of the wedding songs poetics, while on the other hand, the emphasis may be laid onto the dramatic storyline, concentrating on the individual destiny and transformation. Certain features of the ballads allow regarding them as specific narratives of transformation in general, yet grounding of this assumption requires further investigations.